KEABSAHAN PEMBUKTIAN KETERANGAN AHLI DIBACAKAN DALAM PERSIDANGAN PERKARA MELANGGAR KESUSILAAN MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA (Studi Kasus atas Putusan Nomor 476/PID.Sus/2013/PN.Slmn) - Ginanjar Askar Metta, Yuka Destralanda, Gilang Eky Darmawan (GEMA, 2015)
The journal aims to find evidence proving the validity of which was read by a member of the Code of Penal (Criminal Procedure Code) in the case of violation of morality, according to Law No. 11 of 2008 on Information and Electronic Transactions. The approach used in writing this paper is to approach the case. The technique of collecting legal material that is used in this paper is the study of literature. The author uses deductive logic METRODE in writing this journal. Based on the research and pembahasana, it can be concluded that the strength of evidence that expert testimony was read in a matter of decency violation by Act No. 11 of 2008 on Information and Electronic Transactions shall remain valid when didahuli by calling formally by a team of investigators, expert witnesses must be sworn in before giving evidence either orally or in writing (in a letter), and his testimony at trial was conducted in rather than out of the conference.